Natural History of Cystic Vestibular Schwannomas. (July 2023) - Ali, Noor-E-Seher; Sayyid, Zahra N.; Alyono, Jennifer C.
Objective: To determine the natural history of cystic vestibular schwannomas (VS). Study Design: Retrospective cohort. Setting: Single tertiary academic hospital. Patients: Adults diagnosed with cystic VS who had at least 2 MRIs performed at least 6 months apart between 2008 and 2016 with no intervening treatment. Main Outcome Measures: Volumetric growth rates of both the entire tumor and individual cystic and solid components were measured. Linear growth rate of the entire tumor was assessed using the largest diameter parallel to the petrous face at the cerebellopontine angle (CPA). Results: Twenty-one patients met inclusion criteria. The average volumetric growth rate of the tumor was 1.1 ± 2 (range: −1.2 to 7.8), while the average growth rate of the cystic component was 0.8 ± 1.6 (range: −0.5 to 5.3) cm 3 /year. The CPA diameter of the tumor demonstrated an average linear growth rate of was 1.2 ± 4.4 (range: −8to 13.5) mm/year. With regards to tumor diameter, 9/21 (42.9%) remained stable, 3/21 (14.2%) decreased in size, while 9/21 (42.9%) increased in size. Conclusions: Cystic tumors demonstrate a wide variability in growth rate. Larger, multi-center studies will be required to further compare this relationship to solid tumors.